High-Contrast and Compact Integrated Wavelength Diplexer Based on Subwavelength Grating Anisotropic Metamaterial for 1550/2000 nm - Danfeng Zhu; Han Ye; Yumin Liu; Jing Li; Zhongyuan Yu (IEEE Photonics Journal)
A high-contrast and compact wavelength diplexer is presented for conventional 1550 nm and emerging 2000 nm based on a subwavelength-grating (SWG) coupler. The SWG silicon waveguide thoroughly blocks the light propagation around 1550 nm but fully supports 2000 nm (extinction ratio: 43.11 dB). This grating type anisotropic metamaterial not only efficiently reduces the coupling length but also expands the operational bandwidth. Simulated by 3D finite-difference time-domain method, the proposed diplexer possesses a remarkably low insertion loss and a high contrast of 25.24 (31.7) dB at 1550 (2000) nm. The operational bandwidth of 200 (108) nm is achieved with contrast over 15 dB and insertion loss below 0.22 dB. The footprint of diplexer is only 5.27 μm × 11.85 μm. Moreover, such design has the scalability by simply tuning the geometrical parameters of SWG.